An AR Technology Adoption in BeautyCam on Shopee: TAM-Based Literature Review: Literature Review of Adoption Augmented Reality - Anastasya, Ellyn; Religia, Yoga (Faculty of Islamic Economics and Business, Madura Islamic State University, 2025)
This study examines factors influencing the intention to use Augmented Reality (AR) technology in the BeautyCam feature of the Shopee app, based on Fred Davis's TAM model (1989). Conducting a targeted literature published between 2020 and 2024, the study identifies three critical TAM dimensions—perceived usefulness, perceived ease of use, and attitude toward using—that shape behavioral intention to adopt AR technology. The findings highlight the potential for AR technology to be monetized and standardized through these dimensions. The TAM model serves as a theoretical framework to understand user adoption and usage behaviors, offering insights into the critical elements for successful technology integration. As a practical application, it aims to bridge the gap between scientific knowledge and AR application strategies, with the goal of improving the user experience and satisfaction with Shopee's BeautyCam feature. It also provides a foundation for future studies on AR technology in e-commerce, contributing to the growing literature on its practical applications.